DIRECTIONS FOR CREATING AND IMPROVING THE QUALITY OF ATTRACTIVE TOURIST PRODUCTS (Marketing Journal, 2025)
The article develops practical proposals for the formation of attractive tourist products and improving their quality, based on the importance of studying the needs of tourists, offering services that meet their requirements, ensuring the participation of local residents in this process, and integrating national values and traditions into the content of tourist products.
Keywords: Tourist product; tourist services; service; quality; hotel; transport; tour operator; infrastructure; tourist resource